Pengaruh Model Pembelajaran Word Square Terhadap Kemampuan Peserta Didik Dalam Menghafal Kosakata Bahasa Arab Kelas IX MTsN 2 Palu - Ika Rezky Handayani; Titin Fatimah; Agung Wicaksono (Program Studi Pendidikan Bahasa Arab (PBA), Universitas Islam Negeri Datokarama Palu, 2023)
The learning process using the word square learning model aims to encourage students' understanding of the subject matter, create a pleasant atmosphere because learning is in the form of games, train disciplined students, stimulate students to think effectively because this learning model can be a driver and reinforcement in the material so that it can improve student learning outcomes. In this regard, this study aims to prove the influence of the Word Square learning model on the ability of students to memorize Arabic vocabulary in class IX MtsN 2 Palu. This type of research is tentative. The focus of this research is teachers in the field of Arabic studies of Madrasah Tsanawiyah Negeri (MTSN) with a sample of 62 people. The research approach used by researchers is a quantitative approach with experimental methods. And for this research design use Pre-Test and Post-Test Control Group Design. The data were analyzed using the SPSS 26 Program with a different test, namely the t-test or the U test (Mann-Whitney). The results show a significant influence of this learning model on students by showing the results obtained with a probability value of < α at a significant level of 95%. And some differences show the average ability to memorize Arabic vocabulary using the model. This explains that these results obtained the mean value in the experimental post-test > than the control class post-test.